2019
DOI: 10.1002/ppul.24438
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation efficiency to exercise in patients with cystic fibrosis

Abstract: Introduction Exercise ventilation efficiency index in cardiopulmonary exercise testing (CPET) is elevated in patients with heart failure providing useful information on disease progression and prognosis. Few data, however, exist for ventilation efficiency index among cystic fibrosis (CF) patients. Aims To assess ventilation efficiency index (ΔVE/ΔVCO2 or V′E/V′CO2 slope) and intercept of ventilation (VE‐intercept) in CF patients with mild, moderate, and severe cystic fibrosis (CF) lung disease. To assess possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Clinicians and physiologists interested in cardiopulmonary exercise testing (CPET) and ventilatory efficiency appreciate adolescent physiological responses to exercise are not directly translational to the adult, and vice‐versa . It follows that while Kampouras et al provides plentiful discussion involving comparisons between their CPET data and those of our group (Van Iterson et al) reported in adult CF, they missed a critical opportunity to dissect the body of evidence so as to underscore why they consider it is reasonable to compare studies of adults with those of adolescents, particularly in CF. This is a key omission because contrary to their CPET interpretations and discussion, it is recognized the V̇ E /V̇CO 2 slope and reported thresholds for adults are not translational to adolescent populations and vice‐versa, ventilatory efficiency inversely relates with adult age, and cardiopulmonary disease exacerbates effects of aging on ventilatory inefficiency .…”
Section: Human Physiology Is Not the Same Across The Aging Spectrummentioning
confidence: 99%
See 4 more Smart Citations
“…Clinicians and physiologists interested in cardiopulmonary exercise testing (CPET) and ventilatory efficiency appreciate adolescent physiological responses to exercise are not directly translational to the adult, and vice‐versa . It follows that while Kampouras et al provides plentiful discussion involving comparisons between their CPET data and those of our group (Van Iterson et al) reported in adult CF, they missed a critical opportunity to dissect the body of evidence so as to underscore why they consider it is reasonable to compare studies of adults with those of adolescents, particularly in CF. This is a key omission because contrary to their CPET interpretations and discussion, it is recognized the V̇ E /V̇CO 2 slope and reported thresholds for adults are not translational to adolescent populations and vice‐versa, ventilatory efficiency inversely relates with adult age, and cardiopulmonary disease exacerbates effects of aging on ventilatory inefficiency .…”
Section: Human Physiology Is Not the Same Across The Aging Spectrummentioning
confidence: 99%
“…Basic human factors, such as female sex and again, increasing adult age, can lead to an elevated V̇ E /V̇CO 2 slope without heeding effects caused by disease . The comparison of V̇ E /V̇CO 2 slope responses across stratifications of percent predicted V̇O 2peak in Kampouras et al also does not account for age since the reference equations used take only into account height. Equally concerning, American Thoracic Society reference equations used by Kampouras et al to calculate percent predicted FEV 1 reflect spirometry of preschool aged children (2‐6 years).…”
Section: Human Physiology Is Not the Same Across The Aging Spectrummentioning
confidence: 99%
See 3 more Smart Citations